Electroencephalography and Magnetoencephalography : c - Dassios, George; Fokas, Athanassios S. (De Gruyter Series in Mathematics and Life Sciences, 2020)
Electroencephalography and magnetoencephalography are the two most efficient techniques to study the functional brain. This book completely aswers the fundamental mathematical question of uniqueness of the representations obtained using these techniques, and also covers many other concrete results for special geometric models of the brain, presenting the research of the authors and their groups in the last two decades.